2018
DOI: 10.1016/j.scitotenv.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Early stage litter decomposition across biomes

Abstract: Through litter decomposition enormous amounts of carbon is emitted to the atmosphere. Numerous large-scale decomposition experiments have been conducted focusing on this fundamental soil process in order to understand the controls on the terrestrial carbon transfer to the atmosphere. However, previous studies were mostly based on site-specific litter and methodologies, adding major uncertainty to syntheses, comparisons and meta-analyses across different experiments and sites. In the TeaComposition initiative, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
159
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 216 publications
(190 citation statements)
references
References 49 publications
15
159
1
2
Order By: Relevance
“…The effect of OM quality is known to be one of the key drivers of litter decomposition [26]. As expected, we found that high quality OM (green tea) was significantly (paired t-test, p < 0.001, n = 13) more decomposed than low quality OM (rooibos tea; Figure 2), confirming the direct influence of OM quality on mass loss rates [18,27]. Average decomposed mass of green tea (high quality organic matter (OM)) and rooibos tea (low quality OM).…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…The effect of OM quality is known to be one of the key drivers of litter decomposition [26]. As expected, we found that high quality OM (green tea) was significantly (paired t-test, p < 0.001, n = 13) more decomposed than low quality OM (rooibos tea; Figure 2), confirming the direct influence of OM quality on mass loss rates [18,27]. Average decomposed mass of green tea (high quality organic matter (OM)) and rooibos tea (low quality OM).…”
Section: Resultssupporting
confidence: 83%
“…The chronosequence approach used in the present study allowed us to isolate time from the other factors controlling this process, namely climatic conditions and soil properties [18]. Our study indicates that converting CT to NT might favor the decomposition of both low and high quality OM during the transition period.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations